The transfer and commercialization program of the Philippine Council for Industry and Energy Research and Development (PCIERD-DOST) from 2001 to 2009 a case study - Tabangcura, Ma. Elena Talingdan (Technology Management Center, 2010)
Technology has become not only an important dimension of national development and growth but also as an essential factor for survival in this competitive world. Expectedly, the development, transfer and commercialization of new technologies have become the focus and are considered as forces to reckon with by countries, both developed and developing, in their national development goals. In the past years, particularly form 2001-2009 under the Arroyo Administration, there had been a strong support from the national government for S&T development. This comes with the realization that a technology-backed national economic agenda would certainly lead to progress, thereby, S&T will be made the foundation of future economic development of the country. In response to this, the Department of Science and Technology (DOST) developed its National S&T Plan 2002-2020 or NSTP 2020 (Annex A) which gives the direction of S&T development in the Philippines for the next 10 years. The Plan is supportive of the visions and goals stated in the Medium-Term Philippine Development Plan (MTPDP) which are : macroeconomic stability with equitable growth based on the free enterprise, agriculture and fisheries modernization with social equity, comprehensive human development, and good governance.